Taxonomic notes on certain species in the subgenus Limbusa Moore of the genus Euthalia Hübner (Lepidoptera, Papilionoidea, Nymphalidae, Limenitinae) from China and adjacent countries - Huang, Si-Yao; Xu, Yong-Qiang; Lu, Di; Lu, Fei (Zootaxa, 2025)
The taxonomy of certain species of the subgenus Limbusa Moore, 1897 of the genus Euthalia Hübner, 1819 from China is updated. Euthalia bellula uedai Yokochi, 2009 stat. rev. is resurrected from the synonym of E. monbeigi Oberthür, 1907 and restored as a valid subspecies of E. bellula Yokochi, 2005. The relationship between E. monbeigi and E. yunnanica Koiwaya, 1996 is discussed. Euthalia tsangpoi H. Huang, 1999 is downgraded to be a subspecies of Euthalia duda Staudinger, 1886, viz. E. duda tsangpoi stat. nov. In addition, the females of Euthalia mingyiae H. Huang, 2002 and E. thawgawa wuzhenjuni H. Huang, 2021 are reported for the first time.